Sex Disparity in Myopia Explained by Puberty Among Chinese Adolescents From 1995 to 2014: A Nationwide Cross-Sectional Study - Xu, Rongbin; Zhong, Panliang; Jan, Catherine; Song, Yi; Xiong, Xiuqin; Luo, Dongmei; Dong, Yanhui; Ma, Jun; Stafford, Randall S. (Frontiers in Public Health, 2022)
Importance: Girls in East Asia shows higher myopia prevalence than boys. Little research has been done on possible mechanism of puberty that could explain the sex difference in myopia. Objective: To evaluate the association between myopia and puberty, and the role of puberty in explaining sex disparity in adolescent myopia. Design, setting, and participants: In this nationwide cross-sectional study, data came from five consecutive national survey from 1995 to 2014 in China. We included 338, 896 boys aged 11 18 and 439, 481 girls aged 9 18. Data analysis was conducted between January 1, 2019, and July 31, 2020. Main Outcomes and Measures: Myopia was defined according to unaided distance visual acuity and subjective refraction; puberty status was defined as menarche or spermarche status (yes/no). The association between myopia and puberty were evaluated by robust Poisson-GEE regression. Mediation analyses were used to quantify how much the sex disparity in myopia could be explained by puberty. Results: Post-menarche girls and post-spermarche boys showed 29% 41% and 8% 19% higher risk of myopia than pre-menarche girls and pre-spermarche boys, respectively. The association remained significant in girls [prevalence ratio (PR)=1.07, 95%CI:1.04 1.10] but disappeared in boys (P>0.05) after adjustment for potential confounders. Girls had 12% 23% higher risk of myopia than boys. 16.71% of the sex disparity in myopia could be explained by girls’ earlier puberty than boys, compared to 11.14% explained by behavioral factors. Conclusion and Relevance: Puberty status is independently associated with myopia in girls but not in boys. A significant proportion of sex disparity in myopia could be explained by girls’ earlier puberty, thus girls may need earlier preventive strategies for myopia than boys.